Ultrasonic examinations of IMT changes in common carotid artery wall - Trawiński, Zbigniew; Powałowski, Tadeusz; Gutkiewicz, Piotr (Archives of Acoustics, 2007)
The paper describes the initial results of examinations of the intima-media thickness (IMT) in the common carotid artery wall. The examinations of the IMT enable the assessment of elastic properties of the arterial wall. Ultrasonic examinations were carried out on healthy volunteers with the use the apparatus Vascular Echo Doppler (VED), designed by the authors to measure the elasticity of arteries. Application of the PDA-14 PC-card (Signatec) allowed for the acquisition of ultrasonic RF signal from the output of the apparatus VED and further analysis of dynamic changes of the IMT during a heart cycle. Changing of the IMT in time as a difference between the instantaneous position of the two tracking slopes of RF echoes was obtained. For this purpose, the zero-crossing method for tracking the phase changes of the two rising slopes of the RF ultrasonic echo was used.